1975
DOI: 10.1029/ja080i016p02217
|View full text |Cite
|
Sign up to set email alerts
|

A sudden vanishing of the ionosphericFregion due to the launch of Skylab

Abstract: Routine Faraday rotation observations of the VHF signal from the geostationary satellite ATS 3 made at Sagamore Hill (Massachusetts) revealed that an unusually large and rapid decay in the ionospheric total electron content (TEC) occurred near 1240 EST on May 14, 1973. The disturbance appeared as a dramatic 'bite-out' of substantial magnitude (>_50%) and duration (of the order of hours) in the expected diurnal TEC curve for that day. Observations from other sites revealed that a 'hole' in the ionospheric F reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
4

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 19 publications
6
110
0
4
Order By: Relevance
“…In particular, plasma cavities observed in the Earth's ionosphere were artificially induced by the exhaust gases of the spacecraft, such as at the time of the Skylab launch in 1973 (Mendillo et al, 1975;Mendillo, 1988). The released H 2 O molecules reacted very efficiently with the atomic ions of the ionosphere (H + or O + ), leading to a local production of molecular ions (H 2 O + or H 3 O + ) whose electron recombination rates are much larger (a factor 1000) than those of atomic ions.…”
Section: A Polar Plasma Cavitymentioning
confidence: 99%
“…In particular, plasma cavities observed in the Earth's ionosphere were artificially induced by the exhaust gases of the spacecraft, such as at the time of the Skylab launch in 1973 (Mendillo et al, 1975;Mendillo, 1988). The released H 2 O molecules reacted very efficiently with the atomic ions of the ionosphere (H + or O + ), leading to a local production of molecular ions (H 2 O + or H 3 O + ) whose electron recombination rates are much larger (a factor 1000) than those of atomic ions.…”
Section: A Polar Plasma Cavitymentioning
confidence: 99%
“…Later, Mendillo et al (1975) found a sudden TEC decrease after the Skylab launch by measuring the Faraday rotation of radio signals from a geostationary satellite, and suggested that the exhaust plume of the rocket chemically influenced the ionosphere. They inferred that H 2 O and H 2 in the exhaust plume became molecular ions by reacting with ambient O + and their dissociative recombination with e − caused electron loss, or the formation of an ionospheric "hole".…”
Section: Introductionmentioning
confidence: 99%
“…Mendillo et al (1975) present beacon-satellite observations of TEC in the vicinity of the trajectory of the Skylab launch while Wand and Mendillo (1984) report Millstone Hill radar observations of the ionospheric e ects of the launch of HEAO-C. Neither of these daytime studies observed any persistent oscillations of the ionosphere following the creation of large-scale ionospheric holes by the launch-vehicle exhaust products at F-region heights.…”
Section: Persistent E Ects Of Arti®cial Ionospheric Perturbationmentioning
confidence: 99%